Does having a culture of giving support financial inclusion? - Tan, Maverick Sze Yuan (Nanyang Technological University, 2022)
There have been studies on the benefits of financial inclusion, and culture as an alternative channel to impact financial inclusion. However, due to the multifaceted nature of culture, there have been no studies done on the impact of culture of giving or philanthropy on financial inclusion. This paper thus aims to propose that encouraging a culture of giving will positively affect financial inclusion. Using a sample of 115 countries, we adopted the Ordinary Least Squares (OLS) approach in running the regressions. Specifically, the OLS regression results indicate that a culture of giving is significantly correlated with financial inclusion, where a one standard deviation increase in the culture of giving is associated with an improvement in the financial inclusiveness of a nation by 0.557 standard deviation units. Subsequently, in order to ensure the robustness of our results, alternative measures of financial inclusion were substituted into the regression model and regressed separately. Empirical results indicate that regardless of the measures of FI used, the culture of giving remains to have a positive correlation with FI, ceteris paribus. Lastly, WGI is substituted with its 3 subcomponents and regressed separately, offering an in-depth analysis with regards to the importance and predictive effects of the different aspects of WGI on FI. Empirical results suggest that Giving Money and Giving Time could be the key areas within a culture of giving to be focused on, as they were statistically significant in predicting FI.